Ferulic acid and human platelet lysate incorporated alginate dialdehyde-gelatin 3D (bio)printable hydrogels with biological activity - Bider, Faina; Klotschan, Artem; Kuth, Sonja; Weisbach, Volker; Boccaccini, Aldo R. (Journal of Applied Polymer Science, 2024)
This study investigates the creation of multifunctional scaffolds based on alginate dialdehyde (ADA) and gelatin (GEL) incorporating ferulic acid (FA), a phytotherapeutic agent with diverse pharmacological properties, and human platelet lysate (HPL). The multimaterial hydrogels were characterized in terms of degradation/swelling behavior showing that HPL decelerates the degradation process of ADA-GEL hydrogels in absence of FA. A FA release study confirmed that the presence of HPL does not affect the FA release ability of ADA-GEL hydrogel. A trinitrobenzenesulfonic acid (TNBS) assay confirmed no influence of HPL on the Schiff's base formation. The addition of HPL was shown to lead to a decrease in stiffness, mechanical stability, and viscosity of ADA-GEL-HPL inks. This effect was also observed for ADA-GEL-HPL inks when investigating their three-dimensional (3D) printing ability. Cytocompatibility tests and a 3D bioprinting study confirmed the beneficial impact of the addition of HPL on MC3T3-E1 cells. Moreover, an antibacterial effect provided by the addition of FA was confirmed while the incorporation of HPL led to higher VEGF-A expression by MC3T3-E1 cells. Overall, the addition of HPL and FA to ADA-GEL hydrogel results in a promising ink, which has potential for future biofabrication applications.
CRIS-Team Scopus Importer:2024-07-26
Keywords: biocompatibility; biodegradable; bioprinting; hydrogels; synthesis and processing techniques